A CRITICAL DISCOURSE ANALYSIS OF HOW MORAL VALUES ARE TAUGHT IN PRIMARY SCHOOL ENGLISH TEXTBOOKS - Daniel Geraldine Pratama Putra; St. Shabibatul Rohmah (Esteem Journal of English Education Study Programme, 2025)
This study critically explores how moral values are incorporated and communicated in the primary school English textbooks “My Next Words Grades 3 and 4.” Using a qualitative research approach, the study applies Critical Discourse Analysis (CDA) to examine both textual and visual components of the textbooks. The objective is to uncover the moral ideologies embedded in the content and assess how these values correspond with broader cultural and educational goals. By analyzing linguistic elements, stories, and images, the study identifies recurring themes such as respect, empathy, and responsibility, while also revealing implicit messages related to cultural norms and social hierarchies. The findings indicate that while the textbooks effectively promote moral education, some portrayals perpetuate stereotypes and fail to include diverse viewpoints. This research enhances our understanding of the connection between language learning and moral development, offering valuable insights for curriculum developers and educators aiming to create more inclusive and ethically enriching educational materials.